2023
DOI: 10.3389/fpsyg.2023.1126826
|View full text |Cite
|
Sign up to set email alerts
|

The patients‘ perspective - a qualitative analysis of experiencing a fracture-related infection

Abstract: IntroductionFracture-related infection is a devastating complication confronting the patient with several challenges. To improve the management and to enhance the patients’ wellbeing the focus of this study was to understand the emotional impact and patients’ experiences during the process to identify challenges, difficulties, and resources. For this, a qualitative content analysis of semi-structured interviews according to Graneheim and Lundman was performed.MethodsIn total n = 20 patients of a German univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The patients reported that meditation and yoga practices served as valuable tools for them to maintain a positive outlook during recovery. 14 While the efficacy of such supplementary therapeutic approaches in FRI patients awaits validation, their incorporation into clinical practice could be a practical and cost-effective measure. In addition, it is well established that patients benefit from the incorporation of multidisciplinary teams, 12 , 31 and the results of this study emphasize the potential of and rationale for including a psychologist as a vital member of the treatment team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients reported that meditation and yoga practices served as valuable tools for them to maintain a positive outlook during recovery. 14 While the efficacy of such supplementary therapeutic approaches in FRI patients awaits validation, their incorporation into clinical practice could be a practical and cost-effective measure. In addition, it is well established that patients benefit from the incorporation of multidisciplinary teams, 12 , 31 and the results of this study emphasize the potential of and rationale for including a psychologist as a vital member of the treatment team.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Moreover, the recurrence of FRI presents a particularly concerning scenario, potentially leading to greater morbidity, prolonged treatment courses, and heightened psychological distress. 14 Notably, a nationwide analysis conducted in Germany revealed that over 25% of all FRIs (1,893 out of 7,158 individuals) had a pre-existing secondary psychological comorbidity according to diagnoses of the International Classification of Diseases (ICD)-10 chapter F. 15 Further, it was observed that the number of patients with psychological comorbidities had increased by 24% over the past decade. 16 …”
Section: Introductionmentioning
confidence: 99%